2010
DOI: 10.1007/s12024-010-9184-7
|View full text |Cite
|
Sign up to set email alerts
|

The medico-legal investigation of sudden, unexpected and/or unexplained infant deaths in South Africa: where are we—and where are we going?

Abstract: Abstract:Purposes: Sudden Infant Death Syndrome (SIDS) has been reported to be the leading cause of death in infants under one year of age in many countries. Unfortunately, a paucity of published research data exists in South Africa, with regard to the incidence of and investigation into the circumstances surrounding Sudden Unexplained Deaths in Infants (SUDI) and/or SIDS. Currently, even though most academic centers conform to a protocol consistent with internationally accepted standards, there exists no nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…Thus far it would appear that only one study has addressed the investigation of SUDI/SIDS in forensic pathology practice. This study showed that there were apparently substantially more cases admitted as SUDIs and a substantially larger number of SIDS cases in the Cape Town -Tygerberg metropolitan region in comparison to the Pretoria metropolitan region [9]. The study also confirmed that no nationally accepted or standardized infant death investigation protocol exists in South Africa, a country with a population in excess of 50 million people.…”
Section: Introductionsupporting
confidence: 61%
“…Thus far it would appear that only one study has addressed the investigation of SUDI/SIDS in forensic pathology practice. This study showed that there were apparently substantially more cases admitted as SUDIs and a substantially larger number of SIDS cases in the Cape Town -Tygerberg metropolitan region in comparison to the Pretoria metropolitan region [9]. The study also confirmed that no nationally accepted or standardized infant death investigation protocol exists in South Africa, a country with a population in excess of 50 million people.…”
Section: Introductionsupporting
confidence: 61%
“…No standard national guidelines exist for examination of these cases [6]. The need for standard national and international protocols to streamline SUDI investigations and facilitate research has been clearly acknowledged internationally [7,8] and in South Africa [5,6].…”
Section: Medico-legal Investigation Into Sudi and Sidsmentioning
confidence: 99%
“…Since SIDS is documented to be higher in the two to four month age group, this could represent a critical developmental period that coincides with a loss of immune protection due to of waning maternally transferred antibodies [5,42].…”
Section: Functional Immaturity Of the Infant Immune System And The Pementioning
confidence: 99%
See 2 more Smart Citations